Fatty acids negatively regulate platelet function through formation of noncanonical 15‐lipoxygenase‐derived eicosanoids. Issue 1 (28th January 2023) - Yamaguchi, Adriana; van Hoorebeke, Christopher; Tourdot, Benjamin E.; Perry, Steven C.; Lee, Grace; Rhoads, Nicole; Rickenberg, Andrew; Green, Abigail R.; Sorrentino, James; Yeung, Jennifer; Freedman, J. Cody; Holman, Theodore R.; et al.
Abstract: The antiplatelet effect of polyunsaturated fatty acids is primarily attributed to its metabolism to bioactive metabolites by oxygenases, such as lipoxygenases (LOX). Platelets have demonstrated the ability to generate 15‐LOX‐derived metabolites (15‐oxylipins); however, whether 15‐LOX is in the platelet or is required for the formation of 15‐oxylipins remains unclear. This study seeks to elucidate whether 15‐LOX is required for the formation of 15‐oxylipins in the platelet and determine their mechanistic effects on platelet reactivity. In this study, 15‐HETrE, 15‐HETE, and 15‐HEPE attenuated collagen‐induced platelet aggregation, and 15‐HETrE inhibited platelet aggregation induced by different agonists. The observed anti‐aggregatory effect was due to the inhibition of intracellular signaling including αIIbβ3 and protein kinase C activities, calcium mobilization, and granule secretion. While 15‐HETrE inhibited platelets partially through activation of peroxisome proliferator‐activated receptor β (PPARβ), 15‐HETE also inhibited platelets partially through activation of PPARα. 15‐HETrE, 15‐HETE, or 15‐HEPE inhibited 12‐LOX in vitro, with arachidonic acid as the substrate. Additionally, a 15‐oxylipin‐dependent attenuation of 12‐HETE level was observed in platelets following ex vivo treatment with 15‐HETrE, 15‐HETE, or 15‐HEPE. Platelets treated with DGLA formed 15‐HETrE and collagen‐induced platelet aggregation was attenuated only in the presence of ML355 or aspirin, but not in the presence of 15‐LOX‐1 or 15‐LOX‐2 inhibitors. Expression of 15‐LOX‐1, but not 15‐LOX‐2, was decreased in leukocyte‐depleted platelets compared to non‐depleted platelets. Taken together, these findings suggest that 15‐oxylipins regulate platelet reactivity; however, platelet expression of 15‐LOX‐1 is low, suggesting that 15‐oxylipins may be formed in the platelet through a 15‐LOX‐independent pathway. Abstract : Overview of the mechanism underlying the inhibitory effect of 15‐oxylipins on platelet reactivity.